The impact of music industry digitalisation on population well-being: Empirical evidence from China. - Chuanyi Liu; Yinghui Wang (PLoS ONE, 2025)
With the profound transformations brought about by digital technology in the global economy and social operations, digital music has emerged as a vital medium for meeting residents' cultural needs, playing a significant role in promoting cultural dissemination and catering to personalized cultural demands. Previous research has mainly focused on the commodity attributes, symbolic functions, and instrumental value of digital music at the micro level, while studies examining the potential impact of music industry digitalization on residents' well-being remain relatively scarce. Addressing this gap, this study empirically investigates the impact and underlying mechanisms of music industry digitalization on residents' happiness by constructing a fixed-effects model based on data from the 2022 China Family Panel Studies (CFPS). The results reveal that: (1) the digitalization of the music industry significantly enhances residents' subjective well-being; (2) digitalization promotes happiness primarily by boosting social participation, increasing social trust, and improving mental health; and (3) compared to residents with higher Internet access frequency, higher educational attainment, and higher economic status, the positive effects of music industry digitalization on happiness are more pronounced among those with lower Internet access frequency, lower education levels, and lower economic status. This study provides new empirical evidence for understanding the social effects of digital cultural consumption and offers important insights for optimizing cultural policies and improving residents' quality of life.